Respuesta :

Answer:

Step-by-step explanation:

Let's simplify step-by-step.

−7b−9+2+5b

=−7b+−9+2+5b

Combine Like Terms:

=−7b+−9+2+5b

=(−7b+5b)+(−9+2)

=−2b+−7

Answer:

=−2b−7

Answer:

  • -2b - 7

Step-by-step explanation:

Given expression:

  • -7b - 9 + 2 + 5b

1. Collect like terms

  • ⇒ -7b - 9 + 2 + 5b
  • ⇒ b(-7 + 5) + (-9 + 2)

2. Add/Subtract if possible

  • ⇒ b(-7 + 5) + (-9 + 2)
  • ⇒ b(-2) + (-7)

3. Open parenthesis

  • ⇒ b(-2) + (-7)
  • -2b - 7

Thus, the simplified expression is -2b - 7.

ACCESS MORE